Icons Protection Function in the Traditional Beliefs of Ukrainian Roma - Зіневич, Наталія (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The article deals with the nature of the Orthodox religiosity of Ukrainian Roma. The historiography problems are defined. The issue of icons protection function in the rites of the life and calendar cycles and in the context of existence of customary law in traditional Roma communities is actualized.